High-thermal-conductivity diamond composite material and preparation method thereof

By functionalizing the diamond, it forms a stable chemical bond with copper, the problem of weak interface bonding between diamond and copper is solved, the thermal conductivity and mechanical properties of the composite material are improved, and the reliability of the material is enhanced.

CN119710410AInactive Publication Date: 2025-03-28青岛德铠重工有限公司 +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411886438.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The weak interface bond between diamond and copper leads to a reduced thermal conductivity of the composite material and increases the risk of interface debonding, affecting the reliability of the material.

Method used

By functionalizing the diamond, oxygen-containing functional groups are generated and covalently modified, so that it can form stable chemical bonds with copper and enhance the adhesion of the interface.

Benefits of technology

The interface compatibility between diamond and copper is improved, the thermal conductivity and mechanical properties of composite materials are improved, the thermal expansion coefficient is reduced, and the reliability of the material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005199422010000061
    Figure BDA0005199422010000061
  • Figure BDA0005199422010000071
    Figure BDA0005199422010000071
Patent Text Reader

Abstract

The invention relates to the technical field of alloys, in particular to a high-thermal-conductivity diamond composite material and a preparation method thereof. The composite material comprises the following raw materials in parts by weight: 60-80 parts of functionalized diamond and 20-40 parts of copper. The invention also provides a preparation method of the composition. Compared with the prior art, the diamond composite material prepared by the invention has the advantages of excellent interface bonding, high thermal conductivity, low thermal expansion rate, strong operability and simple preparation method, and can be used in the fields of electronic packaging and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alloys, and in particular to a high thermal conductivity diamond composite material and a preparation method thereof. Background Art

[0002] In the past few decades, the rapid development of the electronics industry has promoted the integration and size reduction of electronic components. At the same time, with the rapid progress of high-performance electronic devices with high power density, how to effectively dissipate heat has become an increasingly important challenge. Diamond has very good thermal conductivity, which is mainly due to its crystal structure and physical properties. Each carbon atom in diamond is connected to four neighboring carbon atoms by covalent bonds, forming a very stable and compact lattice structure. This structure gives diamond a very high thermal conductivity, one of the highest thermal conductivity substances in nature. The high symmetry of diamond crystals and the highly ordered arrangement of carbon atoms make heat transfer in the lattice almost unhindered, so the heat conduction efficiency is very high. Heat is mainly transmitted in diamond through phonons (lattice vibrations). Due to the stability and hardness of the diamond crystal structure, phonons are subject to little damping when propagating in the lattice, and can transmit heat at a very high speed. Diamond is usually a highly pure and low-defect crystal, which also contributes to its excellent thermal conductivity. In addition, diamond has the advantages of low density and low thermal expansion coefficient, and is a very potential reinforcement material. These excellent properties make diamond have broad application prospects in high temperature, high frequency, radiation resistance and high power devices. Diamond has important application value in the field of thermal management, especially in high-performance electronic packaging materials, heat sinks for laser equipment, thermal management in the aerospace field, etc. However, due to the high cost and brittleness of diamond, single application is subject to certain limitations. Therefore, the current research focus is to combine diamond with other materials to obtain a more economical, practical and plastic thermal conductive material.

[0003] CN102108458A is a diamond / copper high thermal conductivity composite material and a preparation method thereof, the composite material comprises a base material copper, a reinforcement material is a diamond particle coated with chromium or molybdenum or tungsten or titanium, wherein the volume fraction of the reinforcement in the material is 15%-65%, and the preparation method of the composite material is firstly mixing the diamond particles with pure chromium powder or molybdenum powder or tungsten powder or titanium powder in a mixer, and preparing the high thermal conductivity composite material by an electrodeposition process after high temperature treatment. The invention solves the problem of poor bonding of the diamond / copper interface, avoids the problems of diamond graphitization under high temperature conditions, and the prepared composite material has a higher thermal conductivity and a lower thermal expansion coefficient, which can meet the demand for high-power integrated circuit packaging materials.

[0004] CN118653066A belongs to the technical field of composite thermal conductive materials, and specifically relates to a diamond / copper composite thermal conductive material and a preparation method thereof. The invention firstly prepares a modified silane coupling agent by a two-step method, then uses tetraethyl orthosilicate as a reaction raw material and a modified silane coupling agent as a modifier to prepare a modified silica sol, and then uses the modified silica sol to perform surface modification on the mixed powder, thereby improving the dispersibility of diamond powder and copper powder, and forming a chemical bond between the diamond powder and the copper powder, greatly improving the interface bonding force between diamond and copper; at the same time, by controlling the process of vacuum sintering, the interface bonding force between diamond and copper is further improved, and the thermal conductivity, density and mechanical properties of the composite material are significantly improved.

[0005] Composite materials are a combination of two or more components with different chemical properties or different organizational phases. They are a combination of different materials on a macroscopic scale. The existence of interfaces is inevitable, and interfaces are also the key to determining the performance of composite materials. Diamond-reinforced metal-based composites are composite materials that combine artificially synthesized diamond particles with metal matrices. They combine the excellent properties of diamonds such as high thermal conductivity, low density, and low thermal expansion coefficient, as well as the advantages of metals such as good toughness, plasticity, and weldability. Therefore, it is an ideal choice for a new generation of electronic packaging materials, and can effectively transfer the heat generated by electronic devices. However, when diamond is compounded with metal materials, the diamond particles will be randomly distributed in the metal matrix. Therefore, only when a certain strength of interface bonding is formed can the interface effect be fully reflected, and poor interface bonding will affect the material performance. Summary of the invention

[0006] In view of the above-mentioned defects in the prior art, the technical problem to be solved by the present invention is to provide a high thermal conductivity diamond composite material and a preparation method thereof.

[0007] Copper has low thermal conductivity and thermal expansion coefficient, and high melting point, so the composite material obtained by compounding it with diamond will have good thermal conductivity, but copper and diamond are chemically inert, and copper has poor wettability on the surface of diamond, so the interface bonding between the two is weak, which will affect the performance after compounding. Neither a carbide matrix nor a solid solution is formed between diamond and copper. Only mechanical bonding leads to weak interface bonding and many defects such as voids, thereby reducing the thermal conductivity of the composite material. In addition, the thermal stress at the interface of the composite material is caused by the difference in thermal expansion coefficients between diamond and metallic copper, which will manifest as tensile stress during the cooling process. If the interface bonding force is insufficient, the risk of interface debonding will increase during the preparation and use of the composite material, thereby affecting the reliability of the composite material.

[0008] Therefore, the present invention improves the compatibility of the two by functionalizing diamond, and generates oxygen-containing functional groups, including bridging ether (COC), ketone group (C=O) and hydroxyl group (C-OH) by treating diamond and then oxidizing it, and then covalently modifying it to obtain functionalized diamond. Since the functional monomer contains amino group, thiol group, etc., and the amino nitrogen atom has lone pairs of electrons, these lone pairs of electrons enable it to have the ability to form chemical bonds with metal atoms, and the copper atom has an empty d orbital, which can accept the lone pairs of electrons from the nitrogen atom, thereby forming a coordinated covalent bond. In this bonding, the nitrogen atom provides an electron pair and the copper atom provides an empty orbital, and the two together form a stable chemical bond. This bonding action enables the functionalized modified diamond to be tightly attached to the copper surface, thereby enhancing the adhesion of the interface. The sulfur atom has a special electronic structure, and its outer electrons can interact with the electrons of the copper atom, thereby generating adsorption. This adsorption force may involve the overlap and sharing of electron clouds, similar to the formation mechanism of covalent bonds, but the specific bonding properties may be more complex and may include contributions from electrostatic attraction, covalent bonding, and other intermolecular forces. The modified diamond has better interface compatibility with copper, so a high thermal conductivity composite material can be obtained.

[0009] To achieve the above object, the present invention provides a high thermal conductivity diamond composite material, comprising the following raw materials in parts by weight: 60 to 80 parts of functionalized diamond and 20 to 40 parts of copper.

[0010] The method for preparing the functionalized diamond comprises the following steps:

[0011] S1, acid-washing and alkali-washing the diamond and then oxidizing it at high temperature to obtain oxygen-modified diamond;

[0012] S2. Mixing the functional monomer and the oxygen-modified diamond in a medium, and covalently modifying them to obtain functionalized diamond.

[0013] Furthermore, the method for preparing the functionalized diamond comprises the following steps:

[0014] S1. Add diamond to 15 to 30 times the volume of concentrated hydrochloric acid, stir at 80 to 90° C. for 20 to 30 minutes and filter, add to 15 to 20 times the volume of water, stir for 20 to 30 minutes and filter, add to 15 to 20 times the volume of 20 wt% sodium hydroxide aqueous solution, stir for 20 to 30 minutes and filter, dry, and heat in an oxygen atmosphere to obtain oxygen-modified diamond;

[0015] S2. Add the functional monomer to 8 to 10 times the volume of toluene, stir evenly and mix with oxygen-modified diamond, the mass ratio of functional monomer to diamond is 2 to 5:1, stir at 90 to 100°C for 4 to 6 hours, filter, wash and dry after the reaction to obtain functionalized diamond.

[0016] Preferably, the heating temperature in step S1 ranges from 400 to 450° C. and the heating time ranges from 4 to 6 hours.

[0017] Preferably, the functional monomer is one of (3-aminopropyl)trimethoxysilane, mercaptopropyltrimethoxysilane or diethylenetriaminopropyltrimethoxysilane.

[0018] The invention also discloses a method for preparing the high thermal conductivity diamond composite material.

[0019] A method for preparing a high thermal conductivity diamond composite material comprises the following steps:

[0020] Functionalized diamond and copper are added to ethanol, stirred and mixed to obtain a mixture, the filtered and dried mixture is filled into a mold, hot-pressed and sintered in an inert atmosphere, and a high thermal conductivity diamond composite material is obtained after cooling.

[0021] Furthermore, the volume of the ethanol is 10 to 20 times that of the functionalized diamond.

[0022] Furthermore, the hot pressing sintering pressure is 20-30 MPa.

[0023] Furthermore, the temperature of the hot pressing sintering is 800-1000°C.

[0024] Furthermore, the heating rate of the hot pressing sintering is 80-100° C. / min.

[0025] Furthermore, the hot pressing sintering time is 30 to 40 minutes.

[0026] Beneficial effects of the present invention:

[0027] 1. Compared with the prior art, the diamond composite material prepared by the present invention has excellent interface bonding, high thermal conductivity and low thermal expansion coefficient, strong operability, simple preparation method, and can be used in the fields of electronic packaging.

[0028] 2. The present invention improves the compatibility of the two by functionalizing diamond. Diamond is treated and then oxidized to produce oxygen-containing functional groups, which are then covalently modified to obtain functionalized diamond. Since the functional monomer contains amino groups, thiol groups, etc., it can form a bond with copper, resulting in better interface compatibility between the modified diamond and copper, thereby obtaining a high thermal conductivity composite material. DETAILED DESCRIPTION

[0029] Diamond, 100~200μm.

[0030] Copper, 80-100 mesh.

[0031] Example 1

[0032] A method for preparing a high thermal conductivity diamond composite material comprises the following steps, measured in parts by weight:

[0033] 70 parts of functionalized diamond and 30 parts of copper are added to ethanol, the volume of ethanol being 20 times that of the functionalized diamond, and stirred to obtain a mixture. The filtered and dried mixture is filled into a mold, and hot-pressed sintered in an argon atmosphere. The temperature is increased to 900°C at 100°C / min at 25MPa, and the mixture is sintered for 30 minutes at the heat preservation temperature. After cooling, a high thermal conductivity diamond composite material is obtained.

[0034] The method for preparing the functionalized diamond comprises the following steps, measured in parts by weight:

[0035] S1, adding 60 parts of diamond to 25 times the volume of 35wt% concentrated hydrochloric acid, stirring at 85°C for 25 minutes and filtering, adding to 18 times the volume of water, stirring for 25 minutes and filtering, adding to 18 times the volume of 20wt% sodium hydroxide aqueous solution, stirring for 25 minutes and filtering, drying, heating to 450°C in an oxygen atmosphere for oxidation for 5 hours to obtain oxygen-modified diamond;

[0036] S2. Add (3-aminopropyl)trimethoxysilane to 9 times the volume of toluene, stir evenly and mix with oxygen-modified diamond. The mass ratio of (3-aminopropyl)trimethoxysilane to diamond is 3:1. Stir at 95°C for 5h. After the reaction is completed, filter, wash and dry to obtain functionalized diamond.

[0037] Example 2

[0038] The method is substantially the same as Example 1, except that (3-aminopropyl)trimethoxysilane is replaced by mercaptopropyltrimethoxysilane.

[0039] Example 3

[0040] The method is substantially the same as Example 1, except that (3-aminopropyl)trimethoxysilane is replaced by diethylenetriaminopropyltrimethoxysilane.

[0041] Example 4

[0042] It is basically the same as Example 1, the only difference being that the amount of copper is 20 parts by weight.

[0043] Example 5

[0044] It is basically the same as Example 1, the only difference being that the amount of copper is 40 parts by weight.

[0045] Comparative Example 1

[0046] A method for preparing a high thermal conductivity diamond composite material comprises the following steps, measured in parts by weight:

[0047] 70 parts of diamond and 30 parts of copper are added to ethanol, the volume of ethanol being 20 times that of diamond, and stirred to obtain a mixture. The filtered and dried mixture is filled into a mold, and hot-pressed sintered in an argon atmosphere. The temperature is increased to 900°C at 100°C / min at 25MPa, and the mixture is sintered for 30 minutes at the heat preservation temperature. After cooling, a high thermal conductivity diamond composite material is obtained.

[0048] Test Example 1

[0049] The thermal conductivity and thermal expansion coefficient of the high thermal conductivity diamond composite materials prepared in the examples and the comparative examples were tested. The thermal conductivity was measured according to the method in GB / T22588-2008 "Flash Method for Measurement of Thermal Diffusivity or Thermal Conductivity", and the thermal expansion coefficient was measured using a thermal dilatometer. The specific results are shown in Table 1.

[0050] Table 1 Thermal conductivity test of diamond composite materials

[0051]

[0052]

[0053] Thermal conductivity is also called thermal conductivity coefficient. It refers to the temperature difference of 1K (or 1℃) on both sides of a 1m thick material under stable heat transfer conditions. 2 Thermal conductivity is a physical quantity that measures how fast a material conducts heat. The higher the thermal conductivity of a material, the more heat it conducts per unit time under the same temperature gradient. In practical applications, thermal conductivity is used to evaluate the thermal insulation or heat dissipation properties of a material.

[0054] The coefficient of thermal expansion refers to the relative change in length or volume per unit temperature change when a material expands due to heat. The coefficient of thermal expansion reflects the sensitivity of a material to dimensional changes when the temperature changes. Materials with a small coefficient of thermal expansion have relatively small dimensional changes when the temperature changes and good dimensional stability. In structures or equipment composed of multiple materials, it is very important to match the coefficient of thermal expansion. If the coefficients of thermal expansion of different materials are very different, thermal stress may be generated due to different degrees of expansion or contraction when the temperature changes.

[0055] As can be seen from Table 1, the diamond composite material prepared by the embodiment has higher thermal conductivity and more suitable thermal expansion coefficient, while the diamond composite material in the reference example 1 has lower thermal conductivity and larger thermal expansion coefficient, which may be due to the weak interface bonding between the unmodified diamond and copper, so the interface thermal resistance is larger, and the copper matrix plays a leading role in the thermal expansion process, resulting in a higher thermal expansion coefficient. In the embodiment, by modifying diamond, the functional monomer contains amino, sulfhydryl, etc., the amino nitrogen atom has a lone pair of electrons, and these lone pairs of electrons enable it to have the ability to form chemical bonds with metal atoms, and the copper atom has an empty d orbital, which can accept the lone pair of electrons from the nitrogen atom, thereby forming a coordinated covalent bond. In this bonding, the nitrogen atom provides an electron pair, and the copper atom provides an empty orbital, and the two form a stable chemical bond together, and this bonding action enables the functionalized modified diamond to be closely attached to the copper surface, thereby enhancing the adhesion of the interface. The sulfur atom has a special electronic structure, and its outer electrons can interact with the electrons of the copper atom, thereby generating adsorption. This adsorption force may involve the overlap and sharing of electron clouds, which is similar to the formation mechanism of covalent bonds, but the specific bonding properties may be more complex and may include the contribution of electrostatic attraction, covalent bonding and other intermolecular forces. The modified diamond has better interfacial compatibility with copper, so a composite material with high thermal conductivity can be obtained. While Example 1 has amino groups and Example 2 has thiol groups, Example 3 has more amino groups, so the adsorption force with copper may be stronger, resulting in better interfacial bonding, so the thermal conductivity is significantly higher, and the thermal expansion coefficient is also lower. Compared with Examples 4 and 5, Example 1 has a different copper content, and the thermal conductivity also shows corresponding differences. From the test data, it can be seen that Example 1 has the best ratio.

[0056] Test Example 2

[0057] The flexural strength of the diamond composite materials prepared in the examples and control examples was tested with reference to the method in GB / T6569-2006 “Test method for flexural strength of fine ceramics”. The specific results are shown in Table 2.

[0058] Table 2 Mechanical properties test of diamond composite materials

[0059] Experimental protocol Bending strength / MPa Example 1 255.2 Example 2 253.3 Example 3 254.6 Example 4 244.3 Example 5 265.4 Comparative Example 1 200.1

[0060] It can be seen from Table 2 that the bending strength of the embodiment is greater than that of the comparative example 1. This is because when the diamond is compounded with the metal material, the diamond particles are randomly distributed in the metal matrix. Therefore, only when an interface bonding of a certain strength is formed can the effect of the interface be fully reflected. When the interface bonding is poor, the material properties will be affected. The wettability of copper and the diamond surface is very poor. Therefore, direct compounding is bound to affect the mechanical properties of the composite material. In the embodiment, the adsorption force between the diamond surface and copper is improved by functionally modifying the diamond, resulting in a stronger interface bonding between the two. Therefore, the mechanical properties are less affected.

[0061] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A high thermal conductivity diamond composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 60 to 80 parts of functionalized diamond and 20 to 40 parts of copper.

2. The high thermal conductivity diamond composite material according to claim 1, characterized in that: The method for preparing the functionalized diamond comprises the following steps: S1, acid-washing and alkali-washing the diamond and then oxidizing it at high temperature to obtain oxygen-modified diamond; S2. Mixing the functional monomer and the oxygen-modified diamond in a medium, and covalently modifying them to obtain functionalized diamond.

3. The high thermal conductivity diamond composite material according to claim 2, characterized in that: The method for preparing the functionalized diamond comprises the following steps: S1. Add diamond to 15 to 30 times the volume of concentrated hydrochloric acid, stir at 80 to 90° C. for 20 to 30 minutes and filter, add to 15 to 20 times the volume of water, stir for 20 to 30 minutes and filter, add to 15 to 20 times the volume of 20 wt% sodium hydroxide aqueous solution, stir for 20 to 30 minutes and filter, dry, and heat in an oxygen atmosphere to obtain oxygen-modified diamond; S2. Add the functional monomer to 8 to 10 times the volume of toluene, stir evenly and mix with oxygen-modified diamond, the mass ratio of functional monomer to diamond is 2 to 5:1, stir at 90 to 100°C for 4 to 6 hours, filter, wash and dry after the reaction to obtain functionalized diamond.

4. The high thermal conductivity diamond composite material according to claim 3, characterized in that: The heating temperature in step S1 is in the range of 400 to 450° C. and the heating time is 4 to 6 hours.

5. A method for preparing a high thermal conductivity diamond composite material according to any one of claims 1 to 4, characterized in that: The steps include: Functionalized diamond and copper are added to ethanol, stirred and mixed to obtain a mixture, the filtered and dried mixture is filled into a mold, hot-pressed and sintered in an inert atmosphere, and a high thermal conductivity diamond composite material is obtained after cooling.

6. The method for preparing a high thermal conductivity diamond composite material according to claim 5, characterized in that: The volume of the ethanol is 10 to 20 times that of the functionalized diamond.

7. The method for preparing a high thermal conductivity diamond composite material according to claim 5, characterized in that: The hot pressing sintering pressure is 20-30 MPa.

8. The method for preparing a high thermal conductivity diamond composite material according to claim 5, characterized in that: The temperature of the hot pressing sintering is 800-1000°C.

9. The method for preparing a high thermal conductivity diamond composite material according to claim 5, characterized in that: The heating rate of the hot pressing sintering is 80-100° C. / min.

10. The method for preparing a high thermal conductivity diamond composite material according to claim 5, characterized in that: The hot pressing sintering time is 30 to 40 minutes.

Citation Information

Patent Citations

  • Diamond / copper high-thermal conductivity composite material and preparation method thereof

    CN102108458A

  • Preparation method of diamond / copper composite high in heat conduction performance

    CN107916356A

  • Method for preparing inorganic heat-conducting adhesive by taking etched diamond micro powder as filler

    CN113999617A

  • Diamond / copper composite thermal conductive material and preparation method thereof

    CN114192750A

  • High-thermal-conductivity diamond / copper composite material and preparation method thereof

    CN115491537A